Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1034/j.1600-048x.2000.310312.x
|View full text |Cite
|
Sign up to set email alerts
|

Blue Tit song repertoire size, male quality and interspecific competition

Abstract: A recent hypothesis suggested that bird song repertoire size is a reliable indication of male quality because the number of songs emitted by an individual and the expression of many traits important for fitness are highly dependent on developmental conditions. To test this hypothesis, we studied the relationship between song repertoire size and a trait known to be strongly affected by developmental conditions: tarsus length of Blue Tits Parus caeruleus. We studied this relationship in three populations presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Song complexity is often positively correlated with survival and reproduction (e.g. Buchanan et al 1999;Doutrelant et al 2000), and thus generally reflects an adult male's quality. Being indelibly affected by early rearing conditions, song complexity ought to reflect intergenerational effects.…”
Section: Introductionmentioning
confidence: 99%
“…Song complexity is often positively correlated with survival and reproduction (e.g. Buchanan et al 1999;Doutrelant et al 2000), and thus generally reflects an adult male's quality. Being indelibly affected by early rearing conditions, song complexity ought to reflect intergenerational effects.…”
Section: Introductionmentioning
confidence: 99%
“…If larger body size is advantageous for male blackbirds on Helgoland, larger repertoires may signal higher male quality. In blue tits, Doutrelant et al (2000) found stronger positive correlations between tarsus length and repertoire size in two island populations than in one mainland population. The authors suggest that this was due to different levels of interspecific competition for acoustic space, as the relative great tit densities were lower on the island and blue tit repertoire sizes increased with decreasing great tit densities.…”
Section: Discussionmentioning
confidence: 98%
“…This in turn may lead to either inability to accurately produce speciesspecific songs or high variability in renditions of songs. This has already been demonstrated in other species in the Paridae such as in the great tits (Doutrelant et al 2000;Gorissen et al 2005), and also in other species outside of the Paridae (swamp sparrow Melospiza georgiana fNowicki et al 2002), zebra finch (Zann and Cash 2008) and European starling Sturn us vulgaris Spencer et al 2004)). Thus, in the black-capped chickadee, song consistency could provide reliable information about the ability of the signaller to effectively find and secure resources during the post-fledging period.…”
Section: Discussionmentioning
confidence: 88%